Analysis of data quality, scaling assumptions, and reliability of crowd behaviour scale (Analisis kualiti data, andaian penskalaan dan kebolehpercayaan skala kelakuan ramai) - Ramli, Nurulhuda; Abdul Ghani, Noraida; Ahmad Hatta, Zulkarnain; Mohd Hashim, Intan Hashimah; Sulong, Jasni; Mohd Mahudin, Nor Diana; Abdul Rahman, Shukran; Mat Saad, Zarina (Universiti Utara Malaysia, 2016)
Hajj is an annual religious activity that involves a large gathering of people performing the same rituals at the same time within a confined space. Human behaviour in this mass gathering is an important issue of serious concern with life-threatening consequences due to extreme congestion. A new scale was developed as part of a study in understanding observable crowd behaviour in this religious activity. Subscales of crowd behaviour included aggressive behaviour, coping behaviour, defensive behaviour, avoidance behaviour, protective behaviour, tolerant behaviour, and hazardous behaviour. This article reports on the data quality and scaling assumptions under the traditional Likert scaling criteria and the reliability of the scale. The subjects of the survey were 203 respondents who attended the pre-Hajj training program at three different locations in the country. Methods of testing include item-level descriptive statistics, multitrait scaling analysis, and scale reliability. The results showed that one item each within subscales of aggressive, coping, and tolerant behaviour do not meet the Likert scaling criteria. However, all subscales have acceptable level of reliability. The findings from this study can be used to further improve the crowd behaviour scale.